Late recovery of renal function by rituximab in a patient with Wegener’s granulomatosis - Malina, Michal; Schäfer, Betti; Waldherr, Rüdiger; Wühl, Elke; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2013)
BackgroundRituximab has proven effective in the treatment of complicated granulomatosis with polyangiitis (Wegener’s, GPA). Two controlled trials in adults demonstrated beneficial effects of rituximab compared to cyclophosphamide in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis to induce remission and to treat relapses. Pediatric experience with rituximab in GPA is limited; the impact on renal function is unknown.Case-diagnosis/treatmentWe report a female adolescent with GPA and necrotizing glomerulonephritis that lead to end-stage renal disease (ESRD). After 22 months of peritoneal dialysis, she still experienced relapses and major treatment-associated adverse effects. After a single dose of rituximab, she rapidly achieved clinical remission and, unexpectedly, steadily recovered glomerular filtration rate, plateauing at 25 ml/min/1.73 m2. Peritoneal dialysis could be discontinued for 16 months.ConclusionsThis case documents a potent beneficial effect of rituximab on renal manifestation of GPA even in long-established ESRD.